The Lonchaeidae of Vanuatu (Diptera: Schizophora) - Macgowan, Iain (Zootaxa, 2021)
Seven new species of Lonchaeidae in three genera are described from the Pacific island group of Vanuatu namely, Lamprolonchaea vila MacGowan sp. nov., Lonchaea efate MacGowan sp. nov., Lonchaea malekula MacGowan sp. nov., Lonchaea pentecosti MacGowan sp. nov., Lonchaea tanna MacGowan sp. nov., Silba erromango MacGowan sp. nov. and Silba hebridensis MacGowan sp. nov. The lonchaeid fauna of Vanuatu now totals 13 species in three genera. A key to species with illustrations of the male genitalia is provided.